#### 6.2.6 3.1

6.2.6.1 [533] problem number 1
6.2.6.2 [534] problem number 2
6.2.6.3 [535] problem number 3
6.2.6.4 [536] problem number 4
6.2.6.5 [537] problem number 5
6.2.6.6 [538] problem number 6
6.2.6.7 [539] problem number 7
6.2.6.8 [540] problem number 8
6.2.6.9 [541] problem number 9
6.2.6.10 [542] problem number 10
6.2.6.11 [543] problem number 11

##### 6.2.6.1 [533] problem number 1

problem number 533

Problem 2.3.1.1 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $w_x + a e^{\lambda x} w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (y-\frac {a e^{\lambda x}}{\lambda }\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {-a \,{\mathrm e}^{\lambda x}+\lambda y}{\lambda }\right )$

________________________________________________________________________________________

##### 6.2.6.2 [534] problem number 2

problem number 534

Problem 2.3.1.2 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $w_x + \left ( a e^{\lambda x} +b \right ) w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (-\frac {a e^{\lambda x}}{\lambda }-b x+y\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {-a \,{\mathrm e}^{\lambda x}-\left (b x -y \right ) \lambda }{\lambda }\right )$

________________________________________________________________________________________

##### 6.2.6.3 [535] problem number 3

problem number 535

Problem 2.3.1.3 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $w_x + \left ( a e^{\lambda y} +b \right ) w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac {\log \left (\frac {e^{\lambda y}}{a e^{\lambda y}+b}\right )}{b \lambda }-x\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (-\frac {\ln \left (a \,{\mathrm e}^{b \lambda x}+b \,{\mathrm e}^{\left (b x -y \right ) \lambda }\right )}{b \lambda }\right )$

________________________________________________________________________________________

##### 6.2.6.4 [536] problem number 4

problem number 536

Problem 2.3.1.4 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $w_x + \left ( a e^{\lambda y+ \beta x} +b \right ) w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac {\log \left (a \lambda e^{x (b \lambda +\beta )}+\beta e^{\lambda (b x-y)}+b \lambda e^{\lambda (b x-y)}\right )}{b \lambda +\beta }\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {\left (b x -y \right ) \lambda -\ln \left (\frac {1}{a \lambda \,{\mathrm e}^{\beta x +\lambda y}+b \lambda +\beta }\right )}{b \lambda +\beta }\right )$

________________________________________________________________________________________

##### 6.2.6.5 [537] problem number 5

problem number 537

Problem 2.3.1.5 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $w_x + \left ( a e^{\lambda y+ \beta x} +b e^{\gamma x}\right ) w_y = 0$

Mathematica

Failed

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {-a \lambda \left (\int {\mathrm e}^{\frac {b \lambda \,{\mathrm e}^{g x}}{g}+\beta x}d x \right )-{\mathrm e}^{\frac {\left (b \,{\mathrm e}^{g x}-g y \right ) \lambda }{g}}}{\lambda }\right )$

________________________________________________________________________________________

##### 6.2.6.6 [538] problem number 6

problem number 538

Problem 2.3.1.6 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $a e^{\lambda x} w_x + b e^{\beta y} w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac {b e^{-\lambda x}}{a \lambda }-\frac {e^{-\beta y}}{\beta }\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (-\frac {\left (a \lambda \,{\mathrm e}^{\lambda x}-b \beta \,{\mathrm e}^{\beta y}\right ) {\mathrm e}^{-\beta y -\lambda x}}{b \beta \lambda }\right )$

________________________________________________________________________________________

##### 6.2.6.7 [539] problem number 7

problem number 539

Problem 2.3.1.7 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $\left ( a e^{\lambda x} +b \right ) w_x + \left ( c e^{\beta x}+d \right ) w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac {\beta (c+d) \log \left (a e^{\lambda x}+b\right )-\lambda e^{\beta x} \, _2F_1\left (1,\frac {\beta }{\lambda };\frac {\beta +\lambda }{\lambda };-\frac {a e^{\lambda x}}{b}\right )-\beta \lambda (-b y+c x+d x)}{b \beta \lambda }\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (y -\left (\int \frac {c +d +{\mathrm e}^{\beta x}}{a \,{\mathrm e}^{\lambda x}+b}d x \right )\right )$

________________________________________________________________________________________

##### 6.2.6.8 [540] problem number 8

problem number 540

Problem 2.3.1.8 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $\left ( a e^{\lambda x} +b \right ) w_x + \left ( c e^{\beta y}+d \right ) w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (-\frac {\log \left (\left (e^{\beta y}+c+d\right ) e^{\frac {\beta x (c+d)}{b}-\beta y} \left (a e^{\lambda x}+b\right )^{-\frac {\beta (c+d)}{b \lambda }}\right )}{\beta (c+d)}\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {-b \lambda \RootOf \left (\left (-\left (a \,{\mathrm e}^{\lambda x}+b \right )^{\frac {\beta c^{2}}{\left (c +d \right ) b \lambda }} \left (a \,{\mathrm e}^{\lambda x}+b \right )^{\frac {\beta d^{2}}{\left (c +d \right ) b \lambda }} \left (a \,{\mathrm e}^{\lambda x}+b \right )^{\frac {2 \beta c d}{\left (c +d \right ) b \lambda }} {\mathrm e}^{\frac {\beta c y}{c +d}} {\mathrm e}^{\frac {\beta d y}{c +d}}+\left (a \,{\mathrm e}^{\lambda x}+b \right )^{\frac {\left (c +d \right ) \beta }{b \lambda }} {\mathrm e}^{\frac {\mathit {\_Z} d}{c +d}} {\mathrm e}^{\frac {\mathit {\_Z} c}{c +d}}-c \left (a \,{\mathrm e}^{\lambda x}+b \right )^{\frac {\left (c +d \right ) \beta }{b \lambda }}-d \left (a \,{\mathrm e}^{\lambda x}+b \right )^{\frac {\left (c +d \right ) \beta }{b \lambda }}\right ) {\mathrm e}^{\frac {\mathit {\_Z} c}{c +d}}\right )+\left (\left (b y -\left (c +d \right ) x \right ) \lambda +\left (c +d \right ) \ln \left (a \,{\mathrm e}^{\lambda x}+b \right )\right ) \beta }{\left (c +d \right ) b \beta \lambda }\right )$ Has RootOf

________________________________________________________________________________________

##### 6.2.6.9 [541] problem number 9

problem number 541

Problem 2.3.1.9 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $\left ( a e^{\lambda y} +b \right ) w_x + \left ( c e^{\beta x}+d \right ) w_y = 0$

Mathematica

$\left \{\left \{w(x,y)\to c_1\left (\frac {a e^{\lambda y}}{\lambda }+b y-\frac {e^{\beta x}}{\beta }-c x-d x\right )\right \}\right \}$

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {a \beta \,{\mathrm e}^{\lambda y}+\left (\left (b y +\left (-c -d \right ) x \right ) \beta -{\mathrm e}^{\beta x}\right ) \lambda }{\beta \lambda }\right )$

________________________________________________________________________________________

##### 6.2.6.10 [542] problem number 10

problem number 542

Problem 2.3.1.10 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $\left ( a e^{\lambda x} +b e^{\beta y}\right ) w_x + a \lambda e^{\lambda x} w_y = 0$

Mathematica

Failed

Maple

$w \left (x , y\right ) = \mathit {\_F1} \left (\frac {\lambda x -y +\ln \left (-b \,{\mathrm e}^{\beta y -\lambda x}+\left (\beta -1\right ) a \right )}{\beta -1}\right )$

________________________________________________________________________________________

##### 6.2.6.11 [543] problem number 11

problem number 543

Problem 2.3.1.11 from Handbook of ﬁrst order partial diﬀerential equations by Polyanin, Zaitsev, Moussiaux.

Solve for $$w(x,y)$$ $\left ( a e^{\lambda x+\beta y} +c \mu \right ) w_x - \left ( b e^{\gamma x+ mu y}+c \lambda \right ) w_y = 0$

Mathematica

Failed

Maple

sol=()

________________________________________________________________________________________